(untitled) (Academicia Globe: Inderscience Research, 2022)
A diet rich in fat increases the risk of many diseases, which are the leading cause of death in adults. Whenever the higher the percentage of body fat, the higher the risk of cardiovascular disease. In view of the severe damage that affects human health when the level of fat is high, the current review aimed to investigate the negative effects of excessive fat on human health, by reviewing the mechanisms of excessive fat, its complications and methods of treatment, A review of the lipid profile was presented through the definition of cholesterol and lipoproteins of cholesterol, which included Low density lipoproteins (LDL-C), High density lipoprotein cholesterol (HDL-C), and very low density lipoproteins. Very low density lipoproteins (VLDL-C) as well as triglycerides (TG).